223k views
1 vote
Please solve and explain. Photo attached

Please solve and explain. Photo attached-example-1

1 Answer

2 votes


$((x+1)(x-3))/(x^(2))

Solution:

Given expression:


$((36)/(x^(2))+(36)/(x))/((36)/(x-3))

To solve this expression:


$((36)/(x^(2))+(36)/(x))/((36)/(x-3))

Apply the fraction rule:
$(a)/((b)/(c))=(a \cdot c)/(b)


$=(\left((36)/(x^(2))+(36)/(x)\right)(x-3))/(36)

Let us solve
(36)/(x^(2))+(36)/(x).

Least common multiple of
x^(2), x is
x^(2).

Make the denominator same based on the LCM.

So that multiply and divide the 2nd term by x, we get


$(36)/(x^(2))+(36)/(x)=(36)/(x^(2))+(36 x)/(x^(2))


$=(36+36 x)/(x^(2))

Now, multiply by (x - 3).


$(36+36 x)/(x^(2))(x-3)= ((36 x+36)(x-3))/(x^(2))


$(\left((36)/(x^(2))+(36)/(x)\right)(x-3))/(36)=(((36 x+36)(x-3))/(x^(2)))/(36)

Apply the fraction rule:
((b)/(c))/(a)=(b)/(c \cdot a)


$=((36x+36)(x-3))/(x^(2) \cdot 36)


$=(36(x+1)(x-3))/(x^(2) \cdot 36)

Cancel the common factor 36.


$=((x+1)(x-3))/(x^(2))

Hence the solution is
((x+1)(x-3))/(x^(2)).

User Jake Johnson
by
5.3k points